THE EFFECT OF CAPITAL STRUCTURE AND MANAGERIAL OWNERSHIP ON COMPANY VALUE THROUGH FINANCIAL PERFORMANCE IN THE FOOD & BEVERAGE SUB-SECTOR ON THE INDONESIA STOCK EXCHANGE - Muhammad Arif; Nisrul Irawati; Syahyunan (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Abstract The food and beverage industry is a strategic sector that plays an important role in the national economy and attracts considerable attention from investors in the capital market. Firm value reflects market perceptions of a company’s performance and prospects, which are influenced by capital structure, managerial ownership, and financial performance. This study aims to analyze the effect of capital structure and managerial ownership on firm value, the effect of financial performance on firm value, as well as the role of financial performance as an intervening variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data from 13 companies with a total of 65 observations, analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that capital structure has a positive and significant effect on firm value, managerial ownership has a positive and significant effect on firm value, and financial performance has a positive and significant effect on firm value. In addition, capital structure and managerial ownership are found to have a negative and significant effect on financial performance. Furthermore, financial performance is able to mediate the effect of capital structure on firm value as well as the effect of managerial ownership on firm value. These findings indicate that financing decisions and managerial ownership mechanisms not only have a direct impact on firm value but also operate through financial performance as a channel of influence. Therefore, optimal capital structure management and enhanced effectiveness of managerial ownership are important factors in improving firm value in a sustainable manner.